A retrospective analysis of drug resistance in M. tuberculosis and role of CBNAAT, LPA and culture in diagnosis - Wadhwa, Vishal; Kelkar, Rohini; Ramchandran, Shibani; Chadha, Kirti; Jatale, Raj; Patil, Niranjan; Amberkar, Shraddha (International Journal of Research in Medical Sciences, 2022)
Background: Nucleic acid detection has potentially revolutionized diagnosis of tuberculosis and has established as a screening test of choice. However, conclusions on its role in diagnosing extrapulmonary infection and discordance between drug susceptibility reported through culture, Xpert MTB/ RIF, line probe assay require further review. Objectives were to compare positivity rate of Xpert MTB/RIF ULTRA across various sample types; compare drug susceptibility percentage of Mycobacterium tuberculosis (M. tb) across three platforms i.e., culture, Xpert MTB/RIF and LPA Methods: A retrospective analysis of results of samples was undertaken for a period of one year for Xpert MTB/RIF ultra and three years for LPA and susceptibility through MGIT. Results: Xpert MTB/ RIF Ultra showed overall positivity of 26%, with 10% rifampicin resistance; genitourinary sample positivity was 4%. First line LPA recorded 26% Rif resistance and very few Rifampicin indeterminates. Second line LPA revealed 5.4% aminoglycoside resistance and 26% fluoroquinolone resistance. Through MGIT Rif resistance was 18.2%, multidrug resistance 17.5%, isoniazid monoresistance 6.6%, FQ resistance 18.6%, MDR with FQ resistance 18.6%, amikacin resistance 4% and streptomycin resistance 18%. Conclusions: Xpert MTB/ RIF should be used as a test of choice for detection; Rifampicin resistance should be confirmed with LPA. However, for GUN, pleural fluid and GIT tissue samples; an additional culture should be attempted on the primary sample to improve detection rates. Drug resistance detected through LPA should be phenotyped especially for fluoroquinolones. Moxifloxacin and amikacin could be empirical antibiotics of choice over ofloxacin and Kanamycin due to lower resistance percentage recorded for them.